The acute effects of high-intensity cycling exercise on arterial stiffness in adolescent wrestlers - Alpaslan Gencay, O.; Baykara, M.; Demirel, A.; Berk, E.; Gencay, S. (Journal of Human Kinetics, 2019)
The aim of this study was to determine the acute effects of high-intensity cycling exercise on the variables of carotid artery compliance, distensibility and beta stiffness index in elite adolescent wrestlers. The subjects were elite athletes competing in national, European and World Championships, who attended a training camp in the province of Kahramanmaras organized by the Turkish Centre for Olympic Preparation. The study sample comprised 31 male elite wrestlers with a mean age of 15.90 +/- 0.87 years, body height of 165.97 +/- 9.7 cm and body mass of 66.3 +/- 18.45 kg. The arterial stiffness variables of the wrestlers were measured with high-resolution Doppler ultrasonography before and 5 min after 30 s of high-intensity cycling exercise (the Wingate Anaerobic Cycling test). The results showed a statistically significant correlation between mean power performance and carotid artery compliance at the 5th min after a single cycling sprint exercise (p < 0.05). No correlation was determined between peak power and the arterial stiffness variables (p > 0.05). The study results indicate that acute changes in arterial stiffness variables are associated with the performance level of high-intensity cycling exercise in a group of elite adolescent wrestlers.